'I'm Not There Anymore': Film Performance Affects and the Loosening of Narrative. Issue 1 (7th June 2021) - Prokopic, Pavel
Abstract : The film emerged from a wider, AHRC-funded practice-as-research PhD entitled Affective Cinema, which experiments with cinematographic and directorial techniques, and methods of working with performers, in order to generate film structures that disrupt or offset narrative, semiotic and/or spatial coherence by the production of audio-visual affects. In this way, a certain boundary is being explored between the representational and the non-representational, which gives rise to a sense of 'affective significance' – a meaning that is felt before it can be thought.